The Effectiveness Of Benzydamine Hydrochloride Gargle Versus Throat Spray In Post-tonsillectomy Patient: A Randomized Controlled Trial - Siti Asmat Md Arepen; Nor Eyzawiyah Hassan; Norhafiza Mat Lazim; Shahrul Hitam; Irfan Mohamad (Teikyo University School of Medicine, 2024)
ISSN: 03875547 Volume 45, Issue 01, February, 2022